2023
DOI: 10.1038/s41598-023-32545-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of porous microsponges in minimizing myotoxic side effects of simvastatin

Abstract: Simvastatin (SV) is a poorly soluble drug; its oral administration is associated with a significant problem: Myopathy. The present study aims to formulate SV microsponges that have the potential to minimize the myotoxicity accompanying the oral administration of the drug. SV microsponges were prepared by exploiting the emulsion solvent evaporation technique. The % entrapment efficiency (%EE) of the drug approached 82.54 ± 1.27%, the mean particle size of SV microsponges ranged from 53.80 ± 6.35 to 86.03 ± 4.79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Some studies have reported that statin treatment can reduce the expression and activity of the mitochondrial fission proteins Drp1 and Fis1 [ 214 , 215 , 216 ]. However, the results from different studies are conflicting, with some reporting an increase in fission-related proteins/mitochondrial dysfunction and others showing no significant effect of statin treatment [ 213 , 217 , 218 , 219 ]. It is likely that the effects of statins on mitochondrial dynamics vary depending on the specific statin, its dosage, the duration of treatment, and the experimental model or tissue studied.…”
Section: Target Mitochondrial Fission For Antioxidants In Metabolic D...mentioning
confidence: 99%
“…Some studies have reported that statin treatment can reduce the expression and activity of the mitochondrial fission proteins Drp1 and Fis1 [ 214 , 215 , 216 ]. However, the results from different studies are conflicting, with some reporting an increase in fission-related proteins/mitochondrial dysfunction and others showing no significant effect of statin treatment [ 213 , 217 , 218 , 219 ]. It is likely that the effects of statins on mitochondrial dynamics vary depending on the specific statin, its dosage, the duration of treatment, and the experimental model or tissue studied.…”
Section: Target Mitochondrial Fission For Antioxidants In Metabolic D...mentioning
confidence: 99%
“…Microsponges porous nature provides a number of benefits in drug delivery, including controlled release, increased bioavailability, drug protection, targeted delivery, reduced side effects, and taste masking. Because of these characteristics, microsponges are a diverse and useful platform for refining drug formulations and increasing therapeutic effects [4] Research utilizing mitiglinide microsponges for prolonged drug release was prepared via quasi-emulsion solvent diffusion technique. The particle size of the microsponges was found to be ranging between 39.15-215.78 µm with an entrapment efficiency of 76.7 − 98.74% ± 1.37.…”
Section: Introductionmentioning
confidence: 99%
“…Sustain drug release of microsponges is associated with the increased bioavailability of drugs [9] . Microsponges can be employed to incorporate solids and liquids/ oils, which are thermally (up to 130 °C ), physically and chemically stable (pH range of [1][2][3][4][5][6][7][8][9][10][11] without the use of preservatives [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%